2016
DOI: 10.5944/openpraxis.8.1.226
|View full text |Cite
|
Sign up to set email alerts
|

Question-Answer Activities in Synchronous Virtual Classrooms in Terms of Interest and Usefulness

Abstract: Instructors generally convey their face to face habits to synchronous virtual classrooms, but these face to face strategies do not work in these environments. In this sense, the purpose of this study was to investigate the effects of question type and answer format used in synchronous class implementations on perceived interest and usefulness. To do this, questions were asked in different ways and answers were requested in different formats in synchronous virtual sessions. The participants consisted of 28 post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Open-ended questions were highly beneficial for student engagement synchronously. Aydemir et al [48] found that open-ended questions encouraged students to contribute more, including those with limited knowledge of the concept because no answer is right nor wrong and students' interest in participating was increased.…”
Section: Student Engagement and Technology In Higher Educationmentioning
confidence: 99%
“…Open-ended questions were highly beneficial for student engagement synchronously. Aydemir et al [48] found that open-ended questions encouraged students to contribute more, including those with limited knowledge of the concept because no answer is right nor wrong and students' interest in participating was increased.…”
Section: Student Engagement and Technology In Higher Educationmentioning
confidence: 99%
“…In addition to length and syntactic complexity, other indicators for participation are accuracy (Thai & Boers, 2016) and fluency (Ahmed & Alamin, 2014;Portocarrero et al, 2007) in students' production. In online-based studies, interaction is often holistically assessed based on the amount of classroom participation or quantitatively based on the number of words per participation (Aydemir et al, 2016;Weiser et al, 2018).…”
Section: Interaction In Online Learning Platformsmentioning
confidence: 99%
“…According to Kagan (1992), within the scope of the lenience of instructors toward technology use, instructors were found to be prejudiced toward use of technology in contrast with experience and observations. Aydemir et al (2016); the previous lives of students, perceptions, experiences and beliefs influence their opinions with respect to new situations. Therefore, we should remember the expression which supports the notion that when instructors are faced with new technologies they are generally inclined to use this technology in parallel with their previous experiences and beliefs.…”
Section: Introductionmentioning
confidence: 99%